Our Laparoscopic Appendectomy a Retrospective Study Experience at Department of Pediatric Surgery MMC Mardan a Multi Center Study - Muhammad Javed Khan, Jehangir Khan, Kifayat, Sijad-Ur-Rehman, (Pakistan Journal of Medical & Health Sciences, 2023)
Laparoscopic appendectomy is a minimally invasive surgical procedure used to remove the appendix. It is a safe and effective procedure that can be performed in children of all ages. We present our experience at the Department of Pediatric Surgery at Mardan Medical Complex (MMC) in Mardan, Pakistan. Our study was conducted over a period of one year, from January to December 2018, and included a total of 52 patients who underwent laparoscopic appendectomy. The mean age of the patients was 10.5 years, with a range of 5-15 years. The mean operative time was 48 minutes, with a range of 30-90 minutes. The postoperative recovery time was short, with an average of only 2 days. Our data shows that laparoscopic appendectomy is a safe and effective procedure for the removal of the appendix in pediatric patients. It is associated with a shorter hospital stay and quicker recovery time than open appendectomy. The results of our study indicate that laparoscopic appendectomy should be the preferred method of treating appendicitis in children. Material & Methods: A retrospective study was conducted at the Department of Pediatric Surgery at Mardan Medical Complex (MMC) in Mardan, Pakistan. Medical records of all patients who underwent laparoscopic appendectomy from January to December 2018 were reviewed. Data collected included age, gender, duration of operation, postoperative recovery time, and any complications. Results: A total of 52 patients underwent laparoscopic appendectomy during the study period. The mean age of the patients was 10.5 years, with a range of 5-15 years. The majority of the patients (90.4%) were male. The mean operative time was 48 minutes, with a range of 30-90 minutes. The postoperative recovery time was short, with an average of only 2 days. There were no major complications reported during or after the operation. Practical Implication: This study provides evidence that laparoscopic appendectomy is a safe and effective procedure for the removal of the appendix in pediatric patients. It is associated with a shorter hospital stay and quicker recovery time than open appendectomy. The findings of this study suggest that laparoscopic appendectomy should be the preferred method of treating appendicitis in children. It is important for surgeons to be adequately trained in laparoscopic techniques to ensure the best outcomes for their patients. Conclusion: This study shows that laparoscopic appendectomy is a safe and effective procedure for the removal of the appendix in pediatric patients. It is associated with a shorter hospital stay and quicker recovery time than open appendectomy. The results of our study indicate that laparoscopic appendectomy should be the preferred method of treating appendicitis in children. Keywords: Laparoscopic Appendectomy, Pediatric Surgery, Mardan Medical Complex.